The occurrence of c-myc, p53 and Bcl-2 family proteins in the early phase of development of duodenal epithelium - Kylarová, Dana; Vrchovecký, Jan; Holinka, Martin; Erdösová, Bela (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2004)
In last few years, numerous groups of proteins participating in the regulation of cell proliferation, differentiation and death during ontogenesis have been described. In this study we compared the occurrence of Bcl-2, p53 and myc protein families with the level of proliferative activity and apoptosis during development of duodenal epithelium. Paraffin embedded tissues of eight human embryos and foetuses aged from the 6th-18th week of IUD were used. For the detection of apoptotic cells the TUNEL method was performed, the proliferative marker PCNA and all the proteins studied were detected by means of indirect three-step immunohistochemical method. In the 6th and 8th week of intrauterine development we observed isolated TUNEL positive epithelial cells only and this was accompanied by the disperse presence of PCNA as well as by all the studied proteins: Bcl-2, Bax, Bcl-XL, c-myc, N-myc, p53, p63 and p73. In the early foetal period of duodenal development we registered changes in PCNA and TUNEL positivity in accordance with the constitution of the stem cell pool on base of villi, where more numerous Bcl-2 positive cells were also found. The separation of primitive crypts and villi was not accompanied by any differences in distribution of Bax, Bcl-XL, c-myc, N-myc, p63 and p73 proteins between those compartments: all the studied proteins showed dispersed character. P53 rapidly decreased in this period. In the 18th week of intrauterine development the balance between proliferation in crypts and apoptosis of villi epithelium was well established and no p53 positive cells were found. In the presence of Bcl-2, Bax, Bcl-XL, p63 and p73 we did not find any dramatic changes. The myc proteins were restricted within the epithelium of the Lieberkuhn crypts only.
Keywords: protoonkogenní proteiny c-myc; embryo savčí; Epithelium; epitel; Cell Proliferation; Embryo, Mammalian; imunohistochemie; nádorový supresorový protein p53; lidé; Immunohistochemistry; Duodenum; Humans; Tumor Suppressor Protein p53; Proto-Oncogene Proteins c-myc; apoptóza; protoonkogenní proteiny c-bcl-2; proliferace buněk; Proto-Oncogene Proteins c-bcl-2; duodenum; Apoptosis